2000
DOI: 10.1523/jneurosci.20-22-08596.2000
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Presynaptic and Postsynaptic Structures Is Accompanied by Compensatory Increase in Action Potential-Dependent Synaptic Input to Layer V Neocortical Pyramidal Neurons in Aged Rats

Abstract: Reduction in both presynaptic and postsynaptic structures in the aging neocortex may significantly affect functional synaptic properties in this area. To directly address this issue, we combined whole-cell patch-clamp recording of spontaneously occurring postsynaptic currents (PSCs) with morphological analysis of layer V pyramidal neurons in the parietal cortex of young adult (1- to 2-month-old) and aged (28- to 37-month-old) BN x F344 F(1) hybrid rats. Analysis of spontaneous PSCs was used to contrast functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 68 publications
2
36
0
1
Order By: Relevance
“…In PNA animals, PSC frequency was not altered by inhibition of action potential firing by tetrodotoxin, suggesting the frequency increase occurred by means of an activity-independent mechanism. Frequency of PSCs recorded in tetrodotoxin has been shown to be proportional to the synaptic contacts (44). The failure of tetrodotoxin to alter PSC frequency is thus consistent with the hypothesis that PNA increased connectivity between GABAergic and GnRH neurons.…”
Section: Discussionsupporting
confidence: 75%
“…In PNA animals, PSC frequency was not altered by inhibition of action potential firing by tetrodotoxin, suggesting the frequency increase occurred by means of an activity-independent mechanism. Frequency of PSCs recorded in tetrodotoxin has been shown to be proportional to the synaptic contacts (44). The failure of tetrodotoxin to alter PSC frequency is thus consistent with the hypothesis that PNA increased connectivity between GABAergic and GnRH neurons.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests a potential imbalance between excitation and inhibition in hippocampal circuits in favor of inhibition, which would agree with the proposed imbalance towards inhibition as a substrate of aging-associated cognitive impairment (Wong et al, 2006). However, it should be noted that electrophysiological evaluation of excitatory versus inhibitory inputs into cortical pyramidal neurons did not reveal an imbalance with aging (Wong et al, 2000), although previous morphological studies showed that the age-related decline of inhibitory buttons is region-selective within the hippocampus (Shi et al, 2004). In this respect, it is important to keep in mind that the present study only investigated global changes of the density of different presynaptic markers in the whole hippocampus.…”
Section: Resultsmentioning
confidence: 73%
“…The frequency of sEPSCs recorded in the absence of TTX represents the sum of TTX-insensitive miniature EPSCs and TTX-sensitive (action-potential-dependent) EPSCs (Wong et al, 2000). The latter component has been previously demonstrated to be of larger amplitude than the former in layer V cortical pyramidal neurons (Wong et al, 2000;Berretta and Jones, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that the frequency of sEPSCs recorded in the absence of tetrodotoxin (TTX) represents the sum of TTX-insensitive, miniature EPSCs (or mEPSCs) and TTX-sensitive (action-potential-dependent) EPSCs (Wong et al, 2000). There was reason to think that the nicotinic-induced increase in glutamate release might be the latter type of sEPSCs, those mediated by spiking, so we assessed the effects of blocking action potentials and highvoltage-activated calcium channels.…”
Section: Introductionmentioning
confidence: 99%